2018
DOI: 10.3892/etm.2018.5810
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of immunomodulatory activities of Gloeostereum�incaratum polysaccharides in cyclophosphamide-induced immunosuppression mice

Abstract: Abstract. Gloeostereum incarnatum, a precious edible mushroom, displays anti-bacterial and anti-inflammatory activities; however, its immunomodulatory effect has not been studied yet. The present study aimed to investigate whether polysaccharide compositions of G. incarnatum polysaccharides (GIPS) possess immunomodulatory and immuno-enhancing effects in a Cyclophosphamide monohydrate (CTX)-induced BALB/c mice model. The 28-day GIPS administration at doses of 0.1, 0.3 and 0.9 g/kg remarkably reversed the bodywe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…For example, Ganoderma lucidum alleviates intestinal damage induced by indomethacin in mice ( 43 ) and Hericium erinaceus improves testicular damage via its antioxidative effects and regulation of the GPR41/43 receptor in UC rats and Caco-2 cells ( 44 ). Based on the immunomodulatory and anti-inflammatory effects of GI reported previously ( 7 ), the present study successfully confirmed its protective effect against UC in C57BL/6 mice.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For example, Ganoderma lucidum alleviates intestinal damage induced by indomethacin in mice ( 43 ) and Hericium erinaceus improves testicular damage via its antioxidative effects and regulation of the GPR41/43 receptor in UC rats and Caco-2 cells ( 44 ). Based on the immunomodulatory and anti-inflammatory effects of GI reported previously ( 7 ), the present study successfully confirmed its protective effect against UC in C57BL/6 mice.…”
Section: Discussionsupporting
confidence: 86%
“…water for the remaining 21 days. The doses of GI and SASP were selected based on previous studies ( 7 , 33 ) and our preliminary experiments (data not shown). On the 28th day, blood samples were collected from the orbital venous plexus of the mice and the mice were then euthanized by intraperitoneal injection of 100 mg/kg sodium pentobarbital (Xiya Reagent Co., Ltd.); mortality was characterized by cessation of heartbeat ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells are capable of elicit the lysis and death of target cells by producing granzyme and perforins (Voskoboinik et al, 2015). Moreover, NK cells present anti-cancer and antiviral effect by releasing various pro-inflammatory factors involving IFN-γ (Wang et al, 2018;Zhang et al, 2018). Previous studies have shown that ginseng and its major active components are responsible for the chemo-preventive effects following the activated NK cells (Choi et al, 2017;Shin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng has the effect of immunomodulatory enhancing the expression of IL-1 and TNF [26] and Curcuma longa inhibit Th1/Th2 cytokine imbalance and proinflammatory cytokine production [27]. The immune regulation of polysaccharides isolated from natural extracts has also been reported [28, 29]. HemoHIM is a herbal medicine composed of hot water extracts of Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia japonica Miyabe with enhanced crude polysaccharide content, which are active ingredients that enhance immunity and hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%